2020
DOI: 10.7759/cureus.8985
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Post-Operative Infection and Blood Transfusion in Cardiac Surgery

Abstract: Background Blood transfusion is a commonly used therapy in cardiac surgery, whether it is given during the surgery or in the intensive care unit. It is important to evaluate the risks and benefits of exposure to blood transfusion. The use of blood transfusions can influence patient outcome. Previous studies have implicated blood transfusion as a causative factor in post-operative infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The blood consumption of cardiac surgery accounts for a large proportion of the total blood consumption, up to more than 60%, and ranks first in surgical blood consumption. 24 It is much more obvious in patients with aortic dissection than other cardiac surgeries owing to the preoperative thrombosis, consumption of platelets and other coagulation factors, complexity of surgery, and longer CPB time than other cardiac surgery. Therefore, massive hemorrhage and blood transfusion in the perioperative period are also difficult problems for cardiac surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The blood consumption of cardiac surgery accounts for a large proportion of the total blood consumption, up to more than 60%, and ranks first in surgical blood consumption. 24 It is much more obvious in patients with aortic dissection than other cardiac surgeries owing to the preoperative thrombosis, consumption of platelets and other coagulation factors, complexity of surgery, and longer CPB time than other cardiac surgery. Therefore, massive hemorrhage and blood transfusion in the perioperative period are also difficult problems for cardiac surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…38 According to recent studies, more conservative blood transfusion protocols are being used in various centers. 39 Postoperative Infection has been reported the associated controversial risk with blood transfusion. 40 It has been reported that preoperative anemia, morbidity, mortality, and higher hospital costs are associated with increased blood transfusions.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…The identification of these factors is critical to reduce postoperative infections and to establish a special protocol for managing high-risk patients. At the King Faisal Cardiac Center, the rate of postoperative infection has been reported to be 32%, which is extremely high [ 14 ]. In light of this, the aim of this study was to determine the common risk factor related to postoperative infections among patients at the King Faisal Cardiac Center from January 2014 to September 2020.…”
Section: Introductionmentioning
confidence: 99%